Comprehending Behaviors Of The Consumer In Industry 4.0 Revolution: A Research On Smartphone Brands - Sevimece Karadoğan Doruk; Derya Şahin (İletişim Kuram ve Araştırma Dergisi)
Today, when technology transforms and changes in such a way, a great difference is observed in the behaviors of the consumers. Each innovation that is experienced in the world of technology, leads to the transformation of consumers’ perceptions to the same extent and this transformation is felt in every aspect of life. The revolution of Industry 4.0 that involves the life of consumers with its technological aspects, consists of the conglomeration of the innovations that are happened in the technological period and the adaptation of quite many new technologies to the industrial field in digital life. Based on all this information, the research seeks to reveal whether the external factors affecting the acceptance of augmented reality and artificial intelligence applications, show any alteration in the consumers using the different smartphone brands. For this purpose, the survey form, the reliability, and validity of which were ensured, was applied to 499 people. SPSS 21.0 and AMOS 22.0 packaged software were used in the analysis of the data gathered within the scope of this research. As a result of the analysis made, differences were observed in terms of the usages of smartphone brands discussed within the scope of this research by consumers in each variable of perceived ease of use, perceived benefit, perceived quality, intention to use, and usage behavior.